2021
DOI: 10.1101/2021.09.29.462326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic snapshot of plasma samples reveals new pathways implicated in SARS-CoV-2 pathogenesis

Abstract: Despite of the scientific and human efforts to understand COVID-19, there are questions still unanswered. Variations in the metabolic reaction to SARS-CoV-2 infection could explain the striking differences in the susceptibility to infection and the risk of severe disease. Here, we used untargeted metabolomics to examine novel metabolic pathways related to SARS-CoV-2 susceptibility and COVID-19 clinical severity using capillary electrophoresis coupled to a time-of-flight mass spectrometer (CE-TOF-MS) in plasma … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Exercising due caution due to the severity of the disease, a recent study conducted on hospitalized SARS-CoV-2 patients revealed an association between mortality and concurrent abnormalities in NLR and ADMA [45]. This supports the prognostic value of ADMA assessments in these patients, both during hospitalization and throughout the post-COVID syndrome period, which is still not fully understood [46][47][48][49][50]. Although none of our patients had diabetes, we did not conduct HOMA testing.…”
Section: Discussionsupporting
confidence: 57%
“…Exercising due caution due to the severity of the disease, a recent study conducted on hospitalized SARS-CoV-2 patients revealed an association between mortality and concurrent abnormalities in NLR and ADMA [45]. This supports the prognostic value of ADMA assessments in these patients, both during hospitalization and throughout the post-COVID syndrome period, which is still not fully understood [46][47][48][49][50]. Although none of our patients had diabetes, we did not conduct HOMA testing.…”
Section: Discussionsupporting
confidence: 57%
“…For example, RNA viruses such as rhinovirus [49], influenza virus [50], Zika virus [51], Dengue virus [52], hepatitis C virus [53], and human immunodeficiency virus [54] can hijack the TCA cycle during viral replication. Recent studies have established methods for studying the metabolomics of SARS-CoV-2 infection [55][56][57][58]. However, detailed downstream analysis and the role of the identified host pathways during viral replication were not fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Dataset III (dataset from Spain) consisted of plasma samples from COVID-19 patients (n = 254) diagnosed by RT-PCR and the group of healthy volunteers (n = 133) with a negative COVID-19 test result [23]. RT-PCR.…”
Section: Dataset III (Spain Dataset): Lc-ms Analysismentioning
confidence: 99%
“…COVID-19 patients were grouped into the following categories: (i) severe COVID-19: patients who developed severe respiratory syndrome; (ii) moderate COVID-19: patients who have opportunities on chest X-rays and in need of oxygen therapy, (iii) mild COVID-19: patients who were asymptomatic one week after infection with SARS-CoV-2, and who also did not need oxygen therapy. All samples were analyzed by capillary electrophoresis coupled by time-of-ight mass spectrometer (CE-MS), with an electrospray analyzer [23]. The median age of the healthy group was lower [42 patients there was no signi cant difference (52%).…”
Section: Dataset III (Spain Dataset): Lc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation